Filament winding technique, experiment and simulation analysis on tubular structure - Ma, Quanjin; M. R. M., Rejab; Kaige, Jiang; M. S., Idris; M. N., Harith (2018)
Filament winding process has emerged as one of the potential composite fabrication processes with lower costs. Filament wound products involve classic axisymmetric parts (pipes, rings, driveshafts, high-pressure vessels and storage tanks), non-axisymmetric parts (prismatic nonround sections and pipe fittings). Based on the 3-axis filament winding machine has been designed with the inexpensive control system, it is completely necessary to make a relative comparison between experiment and simulation on tubular structure. In this technical paper, the aim of this paper is to perform a dry winding experiment using the 3-axis filament winding machine and simulate winding process on the tubular structure using CADWIND software with 30°,45°,60° winding angle. The main result indicates that the 3-axis filament winding machine can produce tubular structure with high winding pattern performance with different winding angle. This developed 3-axis winding machine still has weakness compared to CAWIND software simulation results with high axes winding machine about winding pattern, turnaround impact, process error, thickness, friction impact etc. In conclusion, the 3-axis filament winding machine improvements and recommendations come up with its comparison results, which can intuitively understand its limitations and characteristics.